2011
DOI: 10.1029/2010gl045903
|View full text |Cite
|
Sign up to set email alerts
|

Unusual enhancement in temperature and ozone vertical distribution in the lower stratosphere observed over Gadanki, India, following the 15 January 2010 annular eclipse

Abstract: Extensive observations on various atmospheric parameters were carried out from Gadanki (13.48°N, 79.18°E), a tropical station in India, during the annular solar eclipse of 15 January 2010. In the present study, we report changes observed in temperature and ozone concentration in the lower stratosphere associated with the eclipse. Unusual enhancements in the temperature of 12.5 K and in ozone concentration of 5.5. mPa are observed around 21 km just after the eclipse. Plausible mechanisms for the observed eclips… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…To date, there have been no comprehensive detailed observations or analysis of mesospheric O 3 during solar eclipses. Most previous studies have focused on the vertical O 3 distribution in the stratosphere [ Ratnam et al ., ; Kumar et al ., ; Manchanda et al ., ] or total column O 3 [ Chakrabarty et al ., ; Zerefos et al ., ; Chudzynski et al ., ; Tzanis , ]. Only a few observations of mesospheric O 3 during solar eclipses have been reported [e.g., Randhawa , ; Agashe and Rathi , ; Connor et al ., ; Kulikov et al ., ], but they were not robust, and little theoretical analysis of the data was performed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there have been no comprehensive detailed observations or analysis of mesospheric O 3 during solar eclipses. Most previous studies have focused on the vertical O 3 distribution in the stratosphere [ Ratnam et al ., ; Kumar et al ., ; Manchanda et al ., ] or total column O 3 [ Chakrabarty et al ., ; Zerefos et al ., ; Chudzynski et al ., ; Tzanis , ]. Only a few observations of mesospheric O 3 during solar eclipses have been reported [e.g., Randhawa , ; Agashe and Rathi , ; Connor et al ., ; Kulikov et al ., ], but they were not robust, and little theoretical analysis of the data was performed.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the ratio of molecular photolysis rates during the eclipse to those before or after the eclipse is almost independent of the effective wavelength for photolysis. It is, therefore, expected that O 3 measurements during the eclipse may provide unique information on O 3 photochemistry in the mesosphere where clear diurnal O 3 variations have been recognized [Ricaud et al, 1996 [Ratnam et al, 2011;Kumar et al, 2011;Manchanda et al, 2012] or total column O 3 [Chakrabarty et al, 1997;Zerefos et al, 2000;Chudzynski et al, 2001;Tzanis, 2005]. Only a few observations of mesospheric O 3 during solar eclipses have been reported [e.g., Randhawa, 1968;Agashe and Rathi, 1982;Connor et al, 1994;Kulikov et al, 2008], but they were not robust, and little theoretical analysis of the data was performed.…”
Section: Introductionmentioning
confidence: 99%
“…Regular launching of ozonesonde every fortnight from National atmospheric Research Laboratory (NARL), Gadanki (13.5 • N, 79.2 • E), has been conducted from 2011 onwards (Akhil Raj et al, 2015), and a special campaign (consisting of seven launchings) was conducted during the 2010 annular eclipse (Ratnam et al, 2011). A very good comparison between Gadanki ozonesonde and Sounding of the Atmosphere using Broadband Emission Radiometry (SABER), Microwave Limb Sounder (MLS), and ERA-Interim has been found above 20 km altitude (Akhil Raj et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The warming was attributed to thermal contraction of the atmosphere, which induces downward movement in the upper troposphere and lower stratosphere and subsequent adiabatic heating. Ratnam et al (2011) also showed warming around 21 km over Gadanki along with enhancement in ozone partial pressure. In the present study also, one should expect the eclipse induced downward motion.…”
Section: Resultsmentioning
confidence: 91%
“…Significant reduction in the total ozone as measured by Brewer spectro-radiometers during the course of solar eclipses has also been reported (Zerefos et al, 2000;Kazadzis et al, 2007). Very recently, Ratnam et al (2011) reported the changes observed in temperature and ozone concentration in the lower stratosphere over Gadanki (13.48 • N,79.18 • E) associated with the annular eclipse of 15 January 2010. These authors observed unusual enhancements in temperature and ozone around 21 km just after the eclipse and these enhancements were attributed to large subsidence and horizontal advection.…”
Section: Introductionmentioning
confidence: 79%